2021
DOI: 10.3390/foods10020268
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Countrywide Field Investigation of Somatic Cell Counts and Total Bacterial Counts in Bulk-Tank Raw Milk in Sheep Flocks in Greece

Abstract: Objectives were to investigate somatic cell counts (SCC) and total bacterial counts (TBC) in the raw bulk-tank milk of sheep flocks in Greece, to study factors potentially influencing increased SCC and TBC in the bulk-tank milk of sheep and to evaluate possible associations of SCC and TBC with milk content. Throughout Greece, 325 dairy sheep flocks were visited for collection of milk sampling for somatic cell counting, microbiological examination and composition measurement. Geometric mean SCC were 0.488 × 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Gonzalo [ 32 ] proposed a somatic cell count lower than 500,000 (5.70 log10 cells/mL) for good-quality milk, whereas the somatic cell count for healthy sheep mammary gland should not exceed 250,000 cells/mL (5.39 log10 cells/mL). Lianou et al [ 16 ] also reported no differences in the somatic cell count in bulk tank milk collected from farms using the intensive or the semi-intensive production system. In the previous study, the somatic cell count expressed as geometric mean was higher in the milk from intensive farms than in that from semi-intensive farms (5.45 × 10 5 vs. 4.50 × 10 5 cells/mL, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonzalo [ 32 ] proposed a somatic cell count lower than 500,000 (5.70 log10 cells/mL) for good-quality milk, whereas the somatic cell count for healthy sheep mammary gland should not exceed 250,000 cells/mL (5.39 log10 cells/mL). Lianou et al [ 16 ] also reported no differences in the somatic cell count in bulk tank milk collected from farms using the intensive or the semi-intensive production system. In the previous study, the somatic cell count expressed as geometric mean was higher in the milk from intensive farms than in that from semi-intensive farms (5.45 × 10 5 vs. 4.50 × 10 5 cells/mL, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…According to the same author, the distribution of farms according to the farming system is 5% nomadic, 50% semi-extensive, 30% semi-intensive, and 15% home-fed. In the recent countrywide study of Lianou et al [ 16 ] on milk hygiene from sheep flocks, the distribution of farms according to the production system was as follows: extensive 7%, semi-extensive 46%, semi-intensive 33%, and intensive 13%. As seen, the application of extensive and semi-extensive systems is declining, whereas the application of the semi-intensive system is increasing, and the application of the intensive system remains constant.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococci are the most frequently recovered bacteria from the milk of sheep flocks [3,4]. Previous studies that examined staphylococcal isolates from bulk-tank milk of sheep farms mostly studied resistance to methicillin, with contrasting results: for example, in Italy, Macori et al [5] reported that 53% of 51 S. aureus recovered from the milk of six sheep farms showed resistance to methicillin, whilst Giacinti et al [6] reported that the prevalence of methicillin-resistant S. aureus among 286 sheep farms was only 0.7%.…”
Section: Introductionmentioning
confidence: 99%
“…The great majority (87%) of staphylococci included biofilm-forming isolates. Specifically for sheep farms, this proportion (89%) was higher than among staphylococci that were recovered from the bulk-tank milk of the same sheep farms (72%) [8]. Biofilm-formation by these isolates had helped them to attach on the teatcups and, thus, survive cleaning.…”
Section: Discussionmentioning
confidence: 92%
“…In total, 255 dairy sheep flocks and 66 dairy goat herds in the 13 administrative regions of Greece were included into the study and visited for a collection of samples and information. Veterinarians that were active in small ruminant health management around Greece were contacted by telephone and asked whether they wished to collaborate in the investigation [4,8]; in total, 46 veterinarians collaborated in this work. The flocks were selected by the collaborating veterinarians on a convenience basis (willingness of farmers to accept a visit by University personnel for an interview and sample collection).…”
mentioning
confidence: 99%